2022
DOI: 10.1002/app.52360
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical biosensor for single virus particle detection based on molecular crowding polyelectrolyte system

Abstract: To improve the effectiveness of the viral infection diagnostic, we offer a new approach of immunochemical biosensors to determine single viral particles by specific antibodies. The antibodies are immobilized on the electrodes in a three-dimensional polymer matrix with several layers of polyelectrolytes on the screen-printed carbon electrode. Non-covalent immobilization of antibodies in successive layers of positively charged polyethyleneimine (PEI) and negatively charged polystyrene sulfonate (PSS) achieves th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The concentrations of the reagents were used in accordance with the method developed earlier for the formation of a polyelectrolyte matrix of PEI and PSS on the surface of screenprinted electrodes [30]. A total of 5 µL of PEI solution (1 mg/mL in water) was spotted onto the silicon surface, dried, and rinsed three times with water to remove excess PEI.…”
Section: Silicon Surface Modification By Polyelectrolytes and Adsorpt...mentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of the reagents were used in accordance with the method developed earlier for the formation of a polyelectrolyte matrix of PEI and PSS on the surface of screenprinted electrodes [30]. A total of 5 µL of PEI solution (1 mg/mL in water) was spotted onto the silicon surface, dried, and rinsed three times with water to remove excess PEI.…”
Section: Silicon Surface Modification By Polyelectrolytes and Adsorpt...mentioning
confidence: 99%
“…Due to the small volume of the hydrogel nanolayer as well as the "tightness" effect, the interaction between molecules in such an environment occurs more quickly than in the volume of the solution. In the process of developing an electrochemical biosensor for the detection of the encephalitis virus, the benefits of immobilizing specific antibodies into the matrix of successive layers of positively charged polyethylenimine (PEI) and negatively charged polystyrene sulfonate (PSS) were recently demonstrated [30].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously suggested an approach for electrochemical immunosensors with a quasi-mobile polyelectrolyte–protein hydrogel interface [ 22 ], including nanofilms [ 23 ]. Hydrogel interfaces based on neutral polyelectrolytes provide reproducible results in complex systems and simple variation of hydrogel composition, which enables facile data collection for machine learning to decrease the limit of detection [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It proves polyelectrolyte effectiveness for the sensitivity increase of the immunosensors compared to the antibody-only modified electrode. Hydrophilic properties of polyelectrolytes in a crowded medium suppressed nonspecific protein adsorption [ 23 ]. We have shown that LbL assembly effectively controls the adsorption of antigens and antibodies conjugated with horseradish peroxidase on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%